Nesfatin-1 Levels in Cardiac Syndrome X Patients - Bolayir, Hasan Ata (Cardiology and Cardiovascular Medicine, 2018)
Background & Aim: Nesfatin-1 is a novel anorectic neuropeptide with potent metabolic regulatory effects. Our aim is to investigate the association of nesfatin-1 levels and cardiac syndrome X (CSX). Methods: The study group consist of 80 patients who underwent coronary angiography and were diagnosed as CSX according to the presence of exercise-induced typical angina pectoris and ischemia on myocardial perfusion scintigraphy with angiographically normal coronary arteries. For control subjects, we recruited 80 healthy genderand age-matched individuals who were seen for health check-ups. Results: The cases had significantly lower levels of Serum Nesfatin-1 than the subjects (p < 0.001). There is significant correlation between low Nesfatin-1 levels and the CSX presence (OR, 0.982; 95% CI; 0.969-0.995; p=0.005). Conclusion: The study results of CSX indicated lower levels of serum Nesfatin-1 compared to the control group. Nesfatin-1 might function as a pathogenic factor for CSX through an inflammatory response as well as an impaired endothelium. We commend this labor to you and expect further research from you on the association of Nesfatin-1 and CSX.